Passive Q-switched fiber laser in C-and S band region using silver nanoparticles as a saturable absorber / Nur E’Zzati Ruslan - Nur E’Zzati , Ruslan (2019)
This research aims to investigate the feasibility of silver-nanoparticles as a saturable absorber (SA) to passively generate Q-switched pulses in C- and S- bands. Previously, passive Q-switched lasers is generated by employing nonlinear polarization rotation (NPR) and semiconductor saturable absorber mirrors (SESAMs). Recently, passive Q switched lasers can also be generated using 2D materials such as single-walled carbon nanotubes (SWCNT), graphene and transition metal dichalcogenides. The performance of silver-nanoparticles saturable absorber will be investigated at C- and S- band regions. Silver-nanoparticles saturable absorber was made into thin film to allow for easy integration into fiber laser cavity. The measured modulation depth and saturation intensity of the silver-nanoparticle SA are 31.6% and 0.54 MW/cm2, respectively. When inserted between fiber ferrules, the silver-nanoparticles SA generated a self-starting passive Q switched lasers operating in C- and S-bands. C-band Q-switched fiber laser has an increasing repetition rate from 19.4 – 74.1 kHz, while the pulsewidth decreased from 8.88 – 3.2 μs as pump power was increased. The laser also showed wavelength tunability from 1552.9 – 1580.2 nm. The repetition rate increased from 29 – 48 kHz, while the pulsewith decreased from 6.8 – 0.8 μs. The wavelength can be tuned from 1493nm to 1500nm. These results demonstrated that silver-nanoparticles is a new 2D material that can be utilized to generate passive Q-switched which can be utilized in various photonic application.